2018
DOI: 10.1139/cjz-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Increased overwinter mortalities of white-tailed deer (Odocoileus virginianus) fawns during a drought year

Abstract: mortality events. In order of importance, survival rates were affected by days since capture, year of drought, age at capture, week post-capture (1/0 indicator), and region. Estimated overwinter (fall through spring) survival rate (± SE) of fawns in both regions during 2010-14 was 0.83 ± 0.04. However, estimated overwinter survival rates were depressed during 2012-13, following the severe drought of 2012 (0.63 ± 0.11 or 0.66 ± 0.11 depending on model). Main causes of mortality were capture-related and predatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Then, we ran a principal component analysis (PCA) on the nineteen bioclimatic variables using the 'ade4' package (Dray and Dufour 2007) to avoid potential collinearity problems. We retained the ones potentially most relevant to the species distribution among highly correlated bioclimatic variables, based on the biological knowledge of the focal species: as the white-tailed deer is sensitive to drought events (Tosa et al 2018), Bio12 (annual precipitation) and Bio17 (precipitation of the driest quarter) were retained; as snowshoe hare and Canada lynx are sensitive to snowfall and snow cover (Hoving et al 2005), Bio11 (mean temperature of the coldest quarter) and Bio19 (rain precipitation of the coldest quarter) were retained; and given that the grey wolf is sensitive to prey distributional changes, the same variables as the ones retained for the white-tailed deer were selected as they also displayed great importance and low correlation for grey wolf (Supplementary material Appendix 1 Fig. A1).…”
Section: Ensemble Forecasting For Species Distributionsmentioning
confidence: 99%
“…Then, we ran a principal component analysis (PCA) on the nineteen bioclimatic variables using the 'ade4' package (Dray and Dufour 2007) to avoid potential collinearity problems. We retained the ones potentially most relevant to the species distribution among highly correlated bioclimatic variables, based on the biological knowledge of the focal species: as the white-tailed deer is sensitive to drought events (Tosa et al 2018), Bio12 (annual precipitation) and Bio17 (precipitation of the driest quarter) were retained; as snowshoe hare and Canada lynx are sensitive to snowfall and snow cover (Hoving et al 2005), Bio11 (mean temperature of the coldest quarter) and Bio19 (rain precipitation of the coldest quarter) were retained; and given that the grey wolf is sensitive to prey distributional changes, the same variables as the ones retained for the white-tailed deer were selected as they also displayed great importance and low correlation for grey wolf (Supplementary material Appendix 1 Fig. A1).…”
Section: Ensemble Forecasting For Species Distributionsmentioning
confidence: 99%
“…A causal relationship between the relatively severe winter of 2009–2010 and subsequent high rates of hunter harvest in fall of 2010 is speculative; however, delayed increases in white‐tailed deer mortality and morbidity following severe weather conditions is documented (Mech et al 1987, Garroway and Broders 2007, Tosa et al 2017). Nixon et al (1991) reported persistent snow depth of ≥15 cm in Illinois limited access to ground forage and reduced the availability of metabolizable energy for deer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, deer consumed fewer plants, and plants of lower forage quality, and often did not meet their nutritional requirements, which had the potential to limit lactation [12]. Reduced lactation can decrease deer numbers either because of neonate starvation or result in smaller and weaker fawns [13]. Bucks responded to reduced food quantity and quality by displaying smaller body size and antler growth, particularly in young males that were still growing [12].…”
Section: Introductionmentioning
confidence: 99%